An evaluation of the impacts of the Sunsweet cooperative’s advertising expenditures - Silva, Jena (Kansas State University, 2010)
The objective of this analysis is to develop a demand model for the Sunsweet Cooperative and from this model, determine if the benefits to Sunweet’s advertising, as measured by the change in revenues, exceed the advertising costs. Weekly retail scanner data from July 20, 2008 through June 13, 2010 were used. Ordinary least squares regression equations were estimated to determine the overall demand for Sunsweet dried prunes. Two different models were estimated, one for Sunsweet’s overall prune demand and another for the Sunsweet’s Ones product. The advertising elasticity for the total dried prune demand was 0.10 and for the Ones product was 0.24. The demand equations demonstrated that Sunsweet’s advertising expenditures are increasing the overall demand for their dried prunes and their specific Ones product. What cannot be determined from the demand estimations is whether increase in revenues was greater than the cost of the advertising program. This is an especially important question for Sunsweet as it can be discerned from the data that Sunsweet’s advertising expenditures are quite large as a fraction of its revenues when compared with other similar food sellers. Using the regression equations, a benefit-cost simulation was conducted. We developed a measure that tells us how much the quantities sold of prunes would be affected by increased advertising expenditures by Sunsweet while taking into account the costs of advertising under an assumption of monopolistic competition. Two different scenarios were evaluated, one with a shutdown condition that did not allow average revenue to be below average cost and another without this shutdown condition. The total Sunsweet prune model resulted in an average benefit cost of 2.143 with the shutdown constraint and 1.845 without the shutdown constraint. The Ones product model resulted in an average benefit-cost estimate of 2.672 with the shutdown constraint and 2.358 without the shutdown constraint. Overall these ratios are good for a company operating under monopolistic competition and suggest that for every dollar spent on the advertising campaign, the average return was near to or greater than $2. Overall our analysis showed that Sunsweet’s advertising expenditures are increasing their overall demand and their benefits of advertising are exceeding their costs of advertising.
Keywords: AN EVALUATION OF THE IMPACTS OF THE SUNSWEET COOPERATIVE’S ADVERTISING EXPENDITURES; Benefit Cost Analysis; Agriculture, General (0473)